2017
DOI: 10.3847/1538-4357/aa6625
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of Coronal Forbidden Lines

Abstract: Since the magnetic field is responsible for most manifestations of solar activity, one of the most challenging problems in solar physics is the diagnostics of solar magnetic fields, particularly in the outer atmosphere. To this end, it is important to develop rigorous diagnostic tools to interpret polarimetric observations in suitable spectral lines. This paper is devoted to analyzing the diagnostic content of linear polarization imaging observations in coronal forbidden lines. Although this technique is restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 50 publications
1
37
0
1
Order By: Relevance
“…• Measurements of magnetic fields in the corona: The Hanle effect is a reduction in the polarization of light when the atoms emitting the light are subject to a magnetic field in a particular direction, and when they have themselves been excited by polarized light. The Hanle effects with polarized light in the corona is notable question for the measure- [92][93][94]. The analysis of the polarized lights due to the Hanle effect for the diagnostic of the coronal magnetic field is still a challenging topic [1].…”
Section: Discussion For Some New Challenges On Measurements Of Solarmentioning
confidence: 99%
“…• Measurements of magnetic fields in the corona: The Hanle effect is a reduction in the polarization of light when the atoms emitting the light are subject to a magnetic field in a particular direction, and when they have themselves been excited by polarized light. The Hanle effects with polarized light in the corona is notable question for the measure- [92][93][94]. The analysis of the polarized lights due to the Hanle effect for the diagnostic of the coronal magnetic field is still a challenging topic [1].…”
Section: Discussion For Some New Challenges On Measurements Of Solarmentioning
confidence: 99%
“…We incorporate non-LTE (NLTE) line formation for a number of elements using grids of departure coefficients. We use all grids available with SME v574 which includes lithium (Li;Lind et al 2009), oxygen (O; Amarsi et al 2016), Na (Lind et al 2011), magnesium (Mg;Osorio et al 2015), Al (Nordlander & Lind 2017), silicon (Si; Amarsi & Asplund 2017), calcium (Ca; Mashonkina et al 2008), titanium (Ti;Sitnova et al 2020), Fe (Amarsi et al 2016) and Ba (Mashonkina et al 2008).…”
Section: Stellar Parameter Analysismentioning
confidence: 99%
“…On the other hand, measurements of linear polarization of some coronal emission lines have been used to map the direction of coronal magnetic fields in the plane of sky (Tomczyk et al, 2008). It has also been demonstrated that the Hanle effect, a process involving modification of polarization by magnetic fields, could be powerful to diagnose the weak magnetic fields in the upper solar atmosphere (e.g., Trujillo Bueno et al, 2002; Li H et al, 2017). All these techniques require a precise measurement of polarization of coronal emission lines (e.g., Qu ZQ et al, 2009, 2017).…”
mentioning
confidence: 99%